ECONOMIC PROSPECTS IN IVORY COAST: ARDLBOUNDS TESTING THE INVESTMENT-FINANCIAL INTERMEDIATION NEXUS - Koffi Prao, Seraphin; Kouakou , Adeline Aya; Kassi , Jean-Claude Kouadio (Economics and Statistics Research Journal (ESRJ), 2024)
Development, Economic Growth, Non-linearity, Financial Intermediation, Developing Countries DOI 10.5281/zenodo.10568475 The nexus between financial development and economic growth has been a focal point of economic discourse since the seminal works of McKinnon (1973) and Shaw (1973). Advocating for financial liberalization policies to bolster economic growth in developing countries, these early propositions sparked a myriad of studies exploring the intricate relationship between financial development and overall economic advancement. The theoretical foundation supporting the positive impact of financial development on growth is rooted in the notion that it enhances resource allocation efficiency, fortifies risk management capabilities, and ultimately amplifies capital productivity. Moreover, it is posited to augment the pool of savings and investment, substantiating its potential as a catalyst for economic development (McKinnon, 1973; King & Levine, 1993; Pagano, 1993; Neusser & Kugler, 1998; Levine & Schmukler, 2004; Calderon & Liu, 2003). The recognized influence of the financial sector on growth operates through two principal channels: capital accumulation and productivity enhancement. The financial system is attributed with five pivotal functions, including savings mobilization, resource allocation, risk management, transaction facilitation, and corporate monitoring (Barry, 2012). However, empirical findings introduce a nuanced perspective, indicating that the nature and extent of the relationship between financial development and growth may hinge on factors such as income levels (Deidda & Fattouh, 2002) or the stage of financial development (Shen & Lee, 2006). These investigations reveal a discernible nonlinearity in the association between financial development and economic growth. Beck & Levine (2003), in their exploration of the relationship between banks, financial markets, and economic development, assert that the development of these financial entities can be beneficial for economic growth under specific conditions. Notably, Deidda & Fattouh (2002) underscore the non-linear dynamics in an endogenous growth model incorporating financial intermediation. Consequently, the impact of intermediation on economic growth emerges as ambiguous, particularly in the context of a nascent banking sector. This abstract provides a comprehensive overview of the theoretical underpinnings, empirical nuances, and non-linear dynamics characterizing the relationship between financial development and economic growth. As scholarship in this domain advances, the recognition of diverse factors shaping this relationship becomes imperative, paving the way for a more nuanced understanding of the complex interplay between financial development and economic advancement.